Running against the devil : a plot to save America from Trump--and Democrats from themselves - Wilson, Rick, 1963- (Crown Forum, 2020)
Donald Trump is exactly the disaster we feared for America. Hated by a majority of Americans, Trump<U+2019>s administration is rocked by daily scandals, and he<U+2019>s embarrassed us at home and abroad. Trump can<U+2019>t win in 2020, right? Wrong. As 2016 proved, Trump can<U+2019>t win, but the Democrats can sure as hell lose. Only one thing can save Trump, and that<U+2019>s a Democratic candidate who runs the race Trump wants them to run instead of the campaign they must run to win in 2020. Wilson combines decades of national political experience and insight in his take-no-prisoners analysis, hammering Trump<U+2019>s destructive and dangerous first term in a case-by-case takedown of the worst president in history and describing the terrifying prospect of four more years of Trump. Like no one else can, Wilson blows the lid off Trump<U+2019>s 2020 Republican war machine, showing the exact strategies and tactics they<U+2019>ll use against the Democratic nominee . . . and how the Democrats can avoid the catastrophe waiting for them if they fall into Trump<U+2019>s trap. Running Against the Devil is sharply funny, brutally honest, and infused with his biting commentary. It<U+2019>s a vital indictment of Trump, a no-nonsense, no-holds-barred road map to saving America, and the guide to making Donald Trump a one-term president.